2013
DOI: 10.3722/cadaps.2013.489-497
|View full text |Cite
|
Sign up to set email alerts
|

Smart Spatial Ontology: Bridging Semantic Ontology to Spatial Topology

Abstract: This paper proposes a feasible approach named "Smart Spatial Ontology" for converting ontological declarations into topological relations and geometric features, which would then assist users to retrieve relevant cases from the case library. The purpose of this project is to extend the knowledge representing abilities of our design case library, which develops smart retrieval of spatial topology within plan drawings for assisting architectural design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In this research, topological relationships are taken to include any relationships between 3D building elements in a model which may enhance information retrieval. These relationships might be strictly topological and concerned with interior/boundary/exterior of 3D components as noted above, more general spatial/directional relationships (Borrmann and Rank, 2009b), or even relationships as they occur in a very general semantic sense, albeit linked to spatial topology (Lin, 2013). In this sense, any two objects in a model sharing the same attribute (for example: two components supplied by the same manufacturer) can be said to be related.…”
Section: Topologymentioning
confidence: 99%
“…In this research, topological relationships are taken to include any relationships between 3D building elements in a model which may enhance information retrieval. These relationships might be strictly topological and concerned with interior/boundary/exterior of 3D components as noted above, more general spatial/directional relationships (Borrmann and Rank, 2009b), or even relationships as they occur in a very general semantic sense, albeit linked to spatial topology (Lin, 2013). In this sense, any two objects in a model sharing the same attribute (for example: two components supplied by the same manufacturer) can be said to be related.…”
Section: Topologymentioning
confidence: 99%
“…To assist users to associate semantic ontologies with spatial topologies, a visual tool named "smart spatial ontology" (SSO) was proposed in previous studies (Lin, 2013). SSO allows users to annotate semantic predicates on spatial topologies, and therefore provides a bridge between the semantic ontologies and spatial topologies of architectural spaces.…”
Section: Semantic Ontology Of Topologymentioning
confidence: 99%
“…This paper is a follow-up study to the two previous projects "STR: Spatial Topology Retrieval" (Lin and Chiu, 2010) and "SSO: Smart Spatial Ontology" (Lin, 2013). This paper aims to develop a visual tool entitled "Visual Architectural Topology" (VAT) for the purpose of encoding architectural topologies within design cases of a house case library termed "OCS: Open Case Study" (Lin and Chiu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, research [5] and [6] focused on annotating data models to support data integration. Research [7] and [8] developed annotation tools to demonstrate the possibility of sharing and reusing the knowledge that is represented in a computer-aided design model. Research [9] and [10] suggested to annotate business process models with semantic contents for assisting designers and analysts in the management of their models.…”
Section: Introductionmentioning
confidence: 99%